Application of electron-optical transducers in thermal nondestructive inspection - Barke V. E.; Vavilov V. P. Vladimir Platonovich; Kosilov M. S.; Kosilov N. S. (1990, 1990)
The article describes a method of calculating the threshold temperature and the temperature resolution of electron-optical transducers with illuminance threshold 10-5-10-6 1x. It is shown theoretically and experimentally that there transducers can be used as thermal flaw detectors for testing objects more than 250°C hot.